2007
DOI: 10.1016/j.jpba.2006.06.029
|View full text |Cite
|
Sign up to set email alerts
|

LC-APCI-MS method for detection and analysis of tryptanthrin, indigo, and indirubin in Daqingye and Banlangen

Abstract: A rapid, selective, and sensitive LC-APCI-MS method is developed in this study for detecting and analyzing tryptanthrin, indigo, and indirubin in daqingye and banlangen, which are, respectively, the leaves and roots of Isatis indigotica and Strobilanthes cusia in traditional Chinese medicine. The detection of the three active components is linear in concentrations ranging from 100 to 1500 ng/mL, the squared correlation coefficient is higher than 0.996, the precision as measured by the relative standard deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 12 publications
6
53
2
2
Order By: Relevance
“…Indirubin results were similar or lower than those in the previous studies (Liau et al 2007;Gilbert et al 2004;Zou and Koh 2007;Chen et al 2011). Indigo content (2.80 mg/ g) was previously reported by our research group (Karaman et al 2016).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Indirubin results were similar or lower than those in the previous studies (Liau et al 2007;Gilbert et al 2004;Zou and Koh 2007;Chen et al 2011). Indigo content (2.80 mg/ g) was previously reported by our research group (Karaman et al 2016).…”
Section: Resultssupporting
confidence: 89%
“…In natural Isatis plants, some indigo precursors and indirubin known as red isomer of indigo were also tested for their genotoxicity (Candido-Bacani et al 2011) and indirubin and its derivatives were reported to possess low toxicity (Zhen et al 2007). Various biological activities including antifebrile, anti-inflammatory, antiviral, antimicrobial, detoxifying purposes, restenosis and skin psoriasis (Hoessel et al 1999;Chiang et al 2013;Liau et al 2007) and antileukemic activity against myelocytic leukemia in Traditional Chinese Medicine (Hoessel et al 1999) have been reported for indirubin and its derivatives (Hoessel et al 1999). Studies with respect to the monitoring the possible toxic effects of plant species are of great concern for public and environmental health for desired sustainable life comfort.…”
Section: Introductionmentioning
confidence: 99%
“…TLC plate는 aluminum plate에 Silica gel 60 F254 가 도포된 것을 사용하였다(Merck, Darmstatt, Germany). 전개액은 chloroform과 acetonitrile을 8.5: (Liau et al, 2007), 발효 과정에서 인디칸의 가수분 해가 완전히 이루어졌는지의 여부 (Angelini et al, 2004;Gilbert et al, 2004;Stoker et al, 1998;Torimoto, 1987) …”
Section: ) Tlc(thin Layer Chromatography) 분석unclassified
“…Immediately before extraction, dried leaf material was grounded. 1.0 g frozen and powdered samples was extracted by Pressurised Liquid Extraction (PLE) with an ASE 200 instrument (Liau et al, 2007). Bagci and Özçelik (2009) investigated fatty acid in the seeds of Isatis tinctoria using GC and HPLC.…”
Section: Extraction and Separationmentioning
confidence: 99%